3DVSAS: 3D virtual space of the academic secretariat - Nuernberg, Josmar (2015)
The 3D Virtual Worlds tools (MV3D) through its characteristics offer the possibility of implementing real spaces to virtual spaces maintaining the same interactive relationship through the sense of immersion. These possibilities are already real and can be verified in existing applications in various sectors, such methodological tools in educational activities, military training in medical and organizational spheres. In this sense the development of this paper presents the proposed virtualization of the academic secretary of the Graduate Program in Computer Science from the Federal University of Santa Maria using virtual worlds, with the OpenWonderland development platform. Virtualization is the possibility of carrying out activities in three-dimensional virtual environment that supported the sense of immersion becomes a new form of interaction between users of the secretariat services. In the research, they were considered two basic actions performed in the current secretariat to be modeled and executed from the virtual world. The activities correspond to the disciplines offering, and the registration, which are performed by two different user groups, teachers and students respectively. The proposal received positive results from the application HCI assessment method, with data collected by the interface inspection by conducting cognitive walkthrough running the sequence of steps or actions required by a user to accomplish a task.